ANALYSIS OF HONORARY TEACHERS’ PERFORMANCE THROUGH SIMPLE ADDITIVE WEIGHTING (SAW) FOR SUPPORTING PERFORMANCE ASSESSMENT DECISION IN VOCATIONAL HIGH SCHOOL 3 TERBANGGI BESAR CENTRAL LAMPUNG - Yussi Kurniasih; Sri Lestari (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Honorary teachers in Vocational High School 3 Terbanggi Besar Central Lampung were the teachers who were in the young age. The honorary teachers frequently worked in other schools so that it affected to their work discipline. The teacher performance assessment was also required to evaluate these honorary teachers. The performance assessment of the honorary teachers had been carried out by using the performance assessment of the State civil servants teachers. There were many components of this teacher performance assessment. Therefore, the teacher performance assessment for the honorary teachers should be made separately from that of State Civil Servant Teachers. The human resource quality was one of the supporting factors to improve the employee performance productivity. The highly-competent human resources were able to support the level of performance. With this performance assessment, the achievements of each employee were identified. Moreover, this was also able to be used by the management as a consideration in determining the best employees. Vocational High School 3 Terbanggi Besar Central Lampung was able to compete with the other public schools. In the implementation of the teacher performance assessment for the honorary teachers, it is expected that the teachers had balanced softskills and hardskills so that they were able to be active and have achievements in both academic and  non-academic fields.  Therefore, Vocational High School 3 Terbanggi Besar Central Lampung was able to identify the teachers who were able to do the work in the academic and non-academic fields.  Keywords: SAW, Teacher Performance Assessement